Report from the Field: LEARNING THROUGH COLLABORATION: A COLLABORATIVE SCHOOL-BASED APPROACH TO FIELD EXPERIENCES - Dempsey, Ruth (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1994)
Recent research on "collaborative cultures" (Biou & Nias, 1992; Fullan & Hargreaves, 1991; Rosenholtz, 1989) has stressed collaborative approaches for working towards change in schools. The development of such approaches, however, requires a movement away from the present dominant paradigm of teacher education as training. This paper reflects on and describes the structure and development of a collaborative school-based approach to field experiences. RÉSUMÉ De récentes recherches sur le rapprochement école-milieu de formation (Biou & Nias, 1992; Fullan & Hargreaves, 1991; Rosenholtz, 1989) insistent de plus en plus sur la valeur des approches de collaboration pour provoquer des changements dans les écoles. Toutefois, le développement de telles approches implique une distanciation du paradigme actuel de la formation à l'enseignement. Cet article décrirt et examine la structure et le développement d'une telle approche de collaboration entre l'école et le milieu de formation.